Utilizing Instagram Social Media on Language Style: An Analysis to Teenagers as Millennial Generations in Their Captions - Dameria Purba; Bloner Sinurat; Herman Herman (Anglophile Journal, 2021)
This research was conducted in the aim to analyze the language style used by millennial generations in social media, instagram, in their daily captions. With Martin Joos' theory, five different language styles were examined. Frozen style is one of them, as are formal style, consulting style, casual and intimate style. The researchers applied qualitative research design to answer the research question and choose content analysis because the result of the data analyzed is the caption the teenager wrote on his Instagram account. The researchers used documentation as the research instrument. The researchers took 30 data from caption posted in January until July 2021. Data from the teen's Instagram caption was used in this study. There are thirty (30) pieces of data total. After conducting this research, it was found that the dominant style type on Instagram is casual style, which accounts for 17 cases (56.7%), formal style accounts for 10%, consultative style accounts for 2 cases (6.7%), intimate style accounts for 3 cases (23.3%), and frozen style accounts for one case (3,3). Participant, setting, and topic all have an impact on the language style you use. Because of the participant, setting, and topic, it may be determined that the teenagers primarily utilized a casual style Keywords: Language Style, Sociolinguistics, Language on Social Media